Biomechanics of para-rowing - Kleshnev, V. (BioRow, 2023)
While most of our publications have been focused on Olympic rowers, we frequently receive questions about Para-rowing. The amount of the data we have on Para-rowers is not large, so we present a case study here on the comparison of Olympic and Para-rowers in singles.